2009
DOI: 10.1111/j.1574-6941.2008.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

High genetic similarity between two geographically distinct strains of the sulfur-oxidizing symbiont ‘Candidatus Thiobios zoothamnicoli’

Abstract: The giant marine ciliate Zoothamnium niveum (Ciliophora, Oligohymenophora) is obligatorily covered by a monolayer of putative chemoautotrophic sulfur-oxidizing (thiotrophic) bacteria. For Z. niveum specimens from the Caribbean Sea it has been demonstrated that this ectosymbiotic population consists of only a single pleomorphic phylotype described as Candidatus Thiobios zoothamnicoli. The goal of our study was to identify and phylogenetically analyse the ectosymbiont(s) of a recently discovered Z. niveum popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Previous studies also reported slow rates of nucleotide substitution in the 16S rRNA gene of various environmentally acquired symbionts, reflecting efficient purifying selection (Peek et al, 1998). Likewise, highly clonal population has also been reported for the environmentally transmitted, symbiotic sulfur-oxidizing gammaproteobacterium of ciliate Zoothamnium (Rinke et al, 2009).…”
Section: Genetic Polymorphismmentioning
confidence: 74%
“…Previous studies also reported slow rates of nucleotide substitution in the 16S rRNA gene of various environmentally acquired symbionts, reflecting efficient purifying selection (Peek et al, 1998). Likewise, highly clonal population has also been reported for the environmentally transmitted, symbiotic sulfur-oxidizing gammaproteobacterium of ciliate Zoothamnium (Rinke et al, 2009).…”
Section: Genetic Polymorphismmentioning
confidence: 74%
“…More recently, our knowledge of the diversity of bacteria associated with ciliates has increased significantly, primarily as a result of extensive molecular investigations of some commonly occurring species of the genera Paramecium and Euplotes. These studies have demonstrated that most bacterial symbionts belong to one of four classes of the phylum Proteobacteria, namely Alphaproteobacteria (including pathogenic Rickettsia) [2,8,9,18,19,21,22,51,59,60,62,64,67,69], Betaproteobacteria [58,63,66,68], Gammaproteobacteria [4,10,48,53] and Deltaproteobacteria [15]. Associations between ciliates and bacteria of other phyla seem to be infrequent, for example, Verrucomicrobia [42] and Firmicutes [54].…”
Section: Introductionmentioning
confidence: 99%
“…Thiobios zoothamnicoli (Rinke et al, 2006). The similarity between this and another population from Calvi, Corsica, was 99.7% (Rinke et al, 2009) and 99.2% to a Pacific population, termed “ectosymbiont of Zoothamnium niveum ” (Kawato et al, 2010). The internal transcribed spacer (ITS) was also highly similar between the Twin Cays and Calvi population (Rinke et al, 2009).…”
Section: The Symbiont Candidatus Thiobios Zoothamnicolimentioning
confidence: 73%
“…The similarity between this and another population from Calvi, Corsica, was 99.7% (Rinke et al, 2009) and 99.2% to a Pacific population, termed “ectosymbiont of Zoothamnium niveum ” (Kawato et al, 2010). The internal transcribed spacer (ITS) was also highly similar between the Twin Cays and Calvi population (Rinke et al, 2009). Genes for the key enzyme in the Calvin Benson cycle for carbon fixation (ribulose 1,5-bisphosphate carboxylase/oxygenase) and for sulfur metabolism (APS reductase, dissimilatory sulfite reductase) were discovered (Rinke et al, 2009).…”
Section: The Symbiont Candidatus Thiobios Zoothamnicolimentioning
confidence: 73%
See 1 more Smart Citation